The enduring nature of the tripartite system of secondary schooling in Germany: Some explanations - Ertl, H; Phillips, D (2000)
This paper suggests explanations for the enduring nature of the tripartite system of secondary education in Germany and the failure to develop the comprehensive school (Gesamtschule) over a long period.